Non-Hodgkin lymphoma. Issue 10091 (15th July 2017) - Armitage, James O; Gascoyne, Randy D; Lunning, Matthew A; Cavalli, Franco
Summary: Lymphomas can affect any organ in the body, present with a wide range of symptoms, and be seen by primary care physicians and physicians from most specialties. They are traditionally divided into Hodgkin's lymphoma (which accounts for about 10% of all lymphomas) and non-Hodgkin lymphoma, which is the topic of this Seminar. Non-Hodgkin lymphoma represents a wide spectrum of illnesses that vary from the most indolent to the most aggressive malignancies. They arise from lymphocytes that are at various stages of development, and the characteristics of the specific lymphoma subtype reflect those of the cell from which they originated. Since this topic was last reviewed in The Lancet in 2012, advances in understanding the biology and genetics of non-Hodgkin lymphoma and the availability of new diagnostic methods and therapies have improved our ability to manage patients with this disorder.